PERANCANGAN BUKU FOTOGRAFI ARSITEKTUR GEREJA KELAHIRAN SANTA PERAWAN MARIA SEBAGAI UPAYA MENGENALKAN PENINGGALAN BANGUNAN BERSEJARAH KEPADA MASYARAKAT - Handayani, Nydia Belinda; Budiardjo, Hardman; Fahminnansih, Fenty (Jurnal Art Nouveau, 2018)
The purpose of this Reserch is to inform the public especially Surabaya people, about history and identification part of buiding Church of The Birth of Santa Perawan Maria Surabaya which are discussed according to science of architecture along with religious meaning and designed through the book of architectural photography